Hubungan antara Kecerdasan Emosi dengan Kecemasan dalam Menghadapi Ujian Nasional 2012 pada Siswa SMA - Atika Puspita Hapsari; Mardiatmi Susilohati; Ruben Dharmawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Anxiety can be experienced by students, especially during preparation for the national examination. Brain performance in learning among students with high anxiety will more likely to degrade. Anxiety can further cause emotion disturbance, sleeping interference, appetite and physical fitness decrease, hence increasing the possibility of failing the final exam. These problems can be anticipated by early identification, regulation, and management of the emotion disturbance. This study aimed to determine the relationship between emotional quotient with anxiety among high school students preparing the national examination. Methods: This was a cross-sectional study using descriptive and analytical approach. The study was conducted at SMA Negeri 1 Tanjung, Brebes, and purposively sampled 12th grade students in 2011/2012 school year. EQ scores were measured using EQ scale, while anxiety scores were measured using TMAS scale. Data were processed using SPSS 17.0 for Windows. Results: Of 287 eligible samples, only 51 students met the inclusion criteria. Analysis from Pearsons product moment correlation showed an r value of -0,681 (p< 0.001). Conclusions: There was a negative relationship between emotional quotient with anxiety among students of SMA Negeri 1 Tanjung, Brebes preparing the 2012 national examination. Keywords: Emotional Quotient, Anxiety, High School National Examination